THE SYSTEM OF NORMATIVE LEGAL REGULATION OF ACCOUNTING OF THE RUSSIAN FEDERATION - Z. Korzovatykh; A. Bykova (Вестник университета)
The problems of legal regulation of the accounting of financial accounting in Russia. Main attention is paid to the system of legal regulation from different points of view, found a link between the concepts of regulatory accounting, property and non-property relations. With this in mind, it presented the economic classification of accounting information users.